The Influence of The Grammarly Application On Improving Students’ Writing Skill - Siti Qoniah Fajriani; Yuyun Bahtiar; Iin Baroroh Ma’arif; Ulfa Wulan Agustina; Luluk Choirun Nisak Nur (SCHOOLAR: Social and Literature Study in Education, 2026)
In education, AI technology has transformed the education curriculum, especially in the fields of technology, science, mathematics, and engineering. This research aims to determine the influence of using the Grammarly application on improving the writing skills of Islamic senior High School Al-Bairuny Jombang students. This research design is a quantitative experimental research design. The type of experimental research design used is a pre-experimental research design. The population of this study is extra-class A group student from class XI, Islamic senior High School Al-Bairuny Jombang, totaling 38 students. The sample for this research is students from the extra-class A1 class XI Islamic senior High School Al-Bairuny Jombang, totaling 20 students. The results show an increase in students' writing abilities. This can be proven by the average pre-test and post-test scores. The pre-test score was 78.25, and the post-test score was 80.90. Based on the findings of this research, it can be seen that using the Grammarly application as a media can have an influence on improving writing skills. Based on the research findings showing improvements in students' writing scores after using Grammarly, future researchers are advised to expand the scope of the study. Rather than focusing on just one group, it would be better to use a more robust experimental design, such as comparing a group of students who used Grammarly with another group who did not.